Nietzsche e a rebelião escrava do ocidente - Moraes, Tiago Dóbos de (2010)
This thesis focuses on explaining the movement called by Nietzsche as "Slave Revolt in Morality", engages throughout the history of the western world, whose remarkable figures were the propagators of Christianity. We intend to elucidate that the said "Revolt.. ", presented by the Nietzschean interpretation, reversed the world bringing and stirring all the symptoms of the human weakness, which becomes clear in his most intense attacks, written in The Genealogy of Morals and The Antichrist. Such outlines of fragility are grouped around the moral concept of Good and Bad, focused on the message displayed by Christianity. This paper aims to address the shift of the valuation form when there was strength, health in the world, represented by Good and Mean, to the degenerative valuation form of Good and Evil. In this case there is the concern with showing the Nietzsche's criticism as a will of power used to destroy the aegis of the winning moral, that of the Good and Evil, as a will of power used to destroy the aegis of the winning moral, that of the Good and Evil, constantly emphasizing the consensual judgment that there isn't in Nietzsche's own work a total disruption of the need and importance of a moral - what would be even an awful distortion of the Nietzschean philosophy -, but the purpose to allow new moral forms moral, this time no longer degenerative